Neoadjuvant Chemotherapy Before Radical Hysterectomy in Cervical Cancer: A Systematic Comparison of Robotic vs Abdominal Approaches - Rizki Wahyuni; Yahya Irwanto (Asian Journal of Health Research, 2025)
Introduction: Cervical cancer remains a leading cause of cancer mortality worldwide. Neoadjuvant chemotherapy (NACT) followed by radical hysterectomy (RH) is increasingly used, but the comparative safety and efficacy of robotic‐assisted versus open abdominal RH after NACT remain unclear.    Material and Methods: This PRISMA‐compliant systematic review (January 2015–March 2025) analyzed randomized and observational studies comparing robotic‐assisted RH (RRH) and open RH (ARH) in women with FIGO IB₂–IIA₂ cervical cancer treated with platinum‐based NACT. The primary endpoints were intraoperative and postoperative complications. Seven studies involving 534 patients (284 minimally invasive vs. 250 open) met the inclusion criteria.    Results: Overall complication rates were similar between groups (15–20%). Minimally invasive surgery (MIS) significantly reduced estimated blood loss by 75–315 mL (p<0.05) and shortened hospital stay by 1–2 days (p<0.01). Operative time was comparable, with minor increases in conventional laparoscopy. In nerve‐sparing procedures, MIS provided faster bladder and bowel recovery (post‐void residual normalization 11 vs. 18 days; time to flatus 39 vs. 56 hours; p<0.01) and improved 1‐year urinary and intestinal quality of life.    Conclusion: Six of seven studies found no difference in disease‐free or overall survival between MIS and open RH. One study reported worse outcomes with RRH among patients with FIGO IIB disease and multi‐agent NACT (HR 2.5–3.0; p<0.05), suggesting risk in higher‐stage, heavily pretreated cases. Overall, robotic‐assisted RH appears to be a safe and effective alternative to open surgery for appropriately selected FIGO IB₂–IIA₂ cervical cancer patients after NACT.